Gender Analysis in the Islamic Law-Based Ecofeminism Movement for Ecosystem Protection - Ihyani Malik; Karimullah, Suud Sarim; Huseyin Okur; Rahman (El-Mashlahah, 2025)
This study analyzes how the principles of Islamic law can be integrated with the ideas of ecofeminism to create more inclusive and sustainable environmental policies. This study uses an intersectional approach with comprehensive literature analysis and gender analysis frameworks to understand how social identity affects women's participation in ecofeminism and environmental protection based on Islamic law principles. The results of the study state that the integration of the principles of ecofeminism and Islamic law has excellent potential to create fair and sustainable environmental policies based on justice ('adl), balance (mizan), and responsibility (khalifah). The concept of khalifah affirms the role of humans as custodians of the earth, provides a theological basis to support environmental conservation and inspires collective responsibility, including the role of women as essential agents. Programs that give women access to land and natural resources increase their participation in agriculture and environmental management, reduce poverty, and strengthen their role as agents of change. However, challenges such as resistance from patriarchal communities, lack of financial and technical support, and the need for ongoing education and training must be overcome. Technology also plays a crucial role in supporting inclusive and sustainable environmental policies.